N-butylamine-modified graphite nanoflakes blended in ferroelectric P(VDF-TrFE) copolymers for piezoelectric nanogenerators with high power generation efficiency. (5th October 2021) - Yang, Tzu-Chuan; Jiang, Yi-Pei; Lin, Ting-Han; Chen, Shih-Hsuan; Ho, Ching-Mei; Wu, Ming-Chung; Wang, Jer-Chyi
Graphical abstract: Highlights: N-butylamine-modified graphite nanoflakes (BMGNFs) are blended in P(VDF-TrFE) films. Enhanced polarization and reduced dielectric loss of P(VDF-TrFE) are achieved by BMGNFs. BMGNF-blended P(VDF-TrFE) MFS capacitors with superb ferroelectricity are obtained. High generating power density of 33.73 mW/m 2 for a 3-MΩ-load nanogenerator is realized. Abstract: In this study, the effects of n-butylamine-modified graphite nanoflakes (BMGNFs) on the crystalline phase transition, ferroelectric behaviors, and piezoelectric energy harvesting properties of poly(vinylidenefluoride-co-trifluoroethylene) (P(VDF-TrFE)) copolymers are investigated. To confirm the blending of BMGNFs in P(VDF-TrFE), X-ray spectroscopy and Fourier-transform infrared spectroscopy (FTIR) are performed. Additionally, X-ray diffraction, FTIR, field-emission scanning electron microscopy, and atomic force microscopy are performed to analyze the crystallization of the polar β-phase of BMGNF-blended P(VDF-TrFE) copolymers. For P(VDF-TrFE) copolymers blended with pure graphite nanoflakes (GNFs), the crystallization of the polar β-phase is enhanced, but a high dielectric loss induced by the leakage current is clearly observed. The dielectric loss can be effectively reduced through the modification of GNFs by n-butylamine, which improves the remnant polarization and coercive electric field of metal-ferroelectric-semiconductor devices. Furthermore, the piezoelectric nanogenerators comprising BMGNF-blended P(VDF-TrFE) copolymers present a high open-circuit output voltage of 4.9 V and a high short-circuit output current of 4.5 μA for more than 500 times of cycling tests, exhibiting a high generating power density of 33.73 mW/m 2 under a load resistance of 3 MΩ. Hence, the P(VDF-TrFE) copolymers blended with n-butylamine-modified GNFs show superior ferroelectric and piezoelectric behaviors, rendering them promising candidates for applications in future organic sensors and self-powered consumer electronics.